(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
This article is devoted to the fertility at the world level from 1975 to 2012 years. Data from the international statistic refer to the fact that there is relation between level of development of society and reproductive behaviour of the population. High level of fertility is associated to the countries, regions that show the level of development. Low level of fertility is faced countries, regions that belong to the group with low level of development. Transition in fertility is related to the transition in economy and in transition is social surrounding, as well. As a very significant changes, that cause changes in the reproductive behaviour are positive changes in the women ’ status and human develo